2013
DOI: 10.1371/journal.pone.0061501
|View full text |Cite
|
Sign up to set email alerts
|

When More Transmission Equals Less Disease: Reconciling the Disconnect between Disease Hotspots and Parasite Transmission

Abstract: The assumed straightforward connection between transmission intensity and disease occurrence impacts surveillance and control efforts along with statistical methodology, including parameter inference and niche modeling. Many infectious disease systems have the potential for this connection to be more complicated–although demonstrating this in any given disease system has remained elusive. Hemorrhagic disease (HD) is one of the most important diseases of white-tailed deer and is caused by viruses in the Orbivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…We also make use a disease data set collated at the University of Georgia which records occurrence of white-tailed deer morbidity and mortality associated with HD at the county level from 1980-present (detailed in Park et al 2013). Here, we restrict our analysis to 2008-2012, in line with data on the Culicoides species identified from light trap surveys.…”
Section: S T U D Y S Y S T E Mmentioning
confidence: 99%
“…We also make use a disease data set collated at the University of Georgia which records occurrence of white-tailed deer morbidity and mortality associated with HD at the county level from 1980-present (detailed in Park et al 2013). Here, we restrict our analysis to 2008-2012, in line with data on the Culicoides species identified from light trap surveys.…”
Section: S T U D Y S Y S T E Mmentioning
confidence: 99%
“…The lack of clinical manifestation may be due to this high seroprevalence. Indeed, Park et al, have demonstrated that areas with intermediate seroprevalence have high number of cases reporting whereas low case reporting was associated with a high seroprevalence (Park et al, 2013). Only one unpublished study has evaluated seroprevalence of BTV infection in small ruminants of Madagascar (Rasamoelina-Andriamanivo, Dakar: UCAR, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In white-tailed deer (Odocoileus virginianus), which is the species most affected by BTV and EHDV in North America, clinical disease and potential population impacts are highly variable throughout their range (Howerth et al 2001). In general, the disease is most severe in more northern latitudes, where HD occurs sporadically and where population immunity is minimal (Howerth et al 2001;Park et al 2013). In contrast, areas of enzootic stability exist in portions of the southwestern US, where high infection rates occur annually, but clinical disease is rarely reported Flacke et al 2004).…”
Section: Introductionmentioning
confidence: 99%